1995
DOI: 10.3109/00365549509032722
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Haemophilus influenzae Isolates from the Respiratory Tract of Patients with Primary Antibody Deficiencies: Evidence for Persistent Colonizations

Abstract: A total of 117 consecutive patients with primary antibody deficiencies were followed for up to 5 years with regard to acute respiratory tract infections. Nontypeable Haemophilus influenzae (NTHI) was the sole pathogen in 61% (202/330) of the samples from which a potential pathogen was recovered. Common variable immunodeficiency (CVI) was the most prevalent condition (27/39 patients) in the group where H. influenzae was isolated. In patients where H. influenzae was not found only 9/78 patients had CVI. 49 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 29 publications
0
10
0
3
Order By: Relevance
“…To our knowledge, no previous studies have reported on the presence of viruses in the lower respiratory tract of patients with primary hypogammaglobulinemia. On the other hand, the presence of bacteria has been documented (13).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no previous studies have reported on the presence of viruses in the lower respiratory tract of patients with primary hypogammaglobulinemia. On the other hand, the presence of bacteria has been documented (13).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all patients have recurrent symptoms of bronchitis, and to a lesser extent sinusitis, usually due to non‐encapsulated Haemophilus influenzae , although streptococci, Moraxella catarrhalis and mycoplasmas are also important pathogens [ 78–80]. Until the late 1970s, most patients developed and eventually died from bronchiectasis.…”
Section: Clinical Managementmentioning
confidence: 99%
“…The bacterial carriage of otopathogens in the NPs of healthy children is quite common (20 to 50%), and carriage rates are 100% during AOM episodes (19,46). To investigate whether or not NP colonization by otopathogens in healthy children influences the expression of sICAM-1, sera were collected from 17 healthy children with bacterial colonization of the NPs and 6 children without bacterial colonization of the NPs.…”
Section: Resultsmentioning
confidence: 99%